Financial intermediaries and emissions trading market development and pricing strategies - Peter Heindl (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2012)
This paper examines the role of intermediaries in quantity regulation theoretically and presents a data application to the EU Emissions Trading Scheme (EU ETS). The choice of regulated firms to trade permits through intermediaries or directly at the exchange is discussed. Permit pricing strategies of intermediaries and possible issues of market power of intermediaries are modeled. Based on empirical data, the model application aims to assess the actual costs (fees, fixed costs) from permit trading, which represent costs of transacting. In a competitive setup, costs are relatively modest with about 1% to 2% of the permit price. In the EU ETS, firms that trade more than 283,000t CO2/year are likely to directly access the exchange while others trade with intermediaries. In the unlikely event of an intermediary having market power, overall costs would be six times higher in the model application. Options for regulated firms to access a permit exchange directly at low costs decrease the costs of transacting considerably in a competitive and non-competitive intermediary market.
urn:nbn:de:bsz:180-madoc-325692
Keywords: Q52; D42; D21; 330; permit trading; financial intermediaries; market power